Acute relapse and poor immunization following COVID-19 vaccination in a rituximab-treated multiple sclerosis patient - Masoud Etemadifar; Amirhossein Akhavan Sigari; Nahad Sedaghat; Mehri Salari; Hosein Nouri (Taylor & Francis Group, 2021)
With the progress of COVID-19 vaccination programs worldwide, some new adverse events associated with the available vaccines may unfold, especially in subpopulations, representatives of whom were not included in phase I, II, and III clinical trials of these vaccines, such as patients with autoimmune diseases, including multiple sclerosis (MS). A 34-year-old woman presented with severe right hemiplegia and ataxia. She was diagnosed with relapsing-remitting MS (RRMS) 13 years ago and treated with rituximab (an anti-CD20 monoclonal antibody) during the last 15 months. She had received her first dose of adenovirus-vectored COVID-19 vaccine Gam-COVID-Vac (Sputnik V) three months after her last infusion of rituximab and three days before experiencing her latest MS relapse episode, preceded by mild symptoms (fatigue, myalgia, generalized weakness, etc.). Magnetic resonance imaging revealed several new periventricular, juxtacortical, brainstem, and cerebellar peduncle lesions. She received corticosteroid therapy for five consecutive days, and her neurological deficits slightly improved. Twenty-one days after receiving the first dose of the vaccine, her anti-SARS-CoV-2 antibodies were below the lower detection limit. However, a decision was made to adhere to the vaccination schedule and not risk the patient's safety against an unfortunate COVID-19 contraction, and thus, she was advised to receive the second Gam-COVID-Vac dose after discontinuation of oral steroid taper. The safety of adenovirus-based vaccines in patients with autoimmune diseases requires further investigation. Meanwhile, clinicians should raise awareness among their patients regarding the potentially limited efficacy of COVID-19 vaccination in those treated with anti-CD20 treatments. After careful, individualized risk-benefit assessments, planning a delay/pause in such treatments to create a time window for patients to receive the vaccine and develop anti-SARS-CoV-2 immunity may be recommended.